Expert System for Diagnosing Dental and Oral Diseases Using the Forward Chaining Method - Alvira, Mise; Yunan, Amsar; Khairuman, Khairuman; Anugreni, Fera; Ilham, Dirja Nur; Bean, Hasbaini; Saputra, Devi Satria (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Dental and oral health is important to pay attention to and is an integral part of overall health that requires immediate treatment before it is too late and can affect a person's health condition. One of the obstacles experienced is the difficulty of diagnosing dental disease in remote areas due to the uneven distribution of experts or dentists. Therefore, in this research, an expert system was built that can diagnose dental disease and tooth-supporting tissue based on knowledge obtained from direct experts. An expert system built on a web basis using the PHP programming language and MySQL database. The problem-solving engine used is the Forward Chaining method. This method can diagnose disease by adjusting the facts experienced with the rules that have been created which are entered into the system.